A 3.8 Å resolution cryo-EM structure of a small protein bound to an imaging scaffold - Yuxi Liu (Nature Portfolio, 2019)
Proteins smaller than about 50 kDa are currently too small to be imaged at high resolution by cryo‐electron microscopy (cryo‐EM). Here authors design a protein scaffold that binds 12 copies of a small 26 kDa protein (GFP), which allowed visualizing GFP at a resolution of 3.8Å by cryo‐EM.